Re-Examining Theories X, Y And Z In The Contemporary Media Industry In Nigeria - Ifeanyi Martins NWOKEOCHA, PhD (Cita konsultindo, 2024)
This paper re-examine the applicability and relevance of Theories X, Y, and Z within the dynamic ladscape of the contemporary media industry in Nigeria. The media sector in Nigeria has undergone profound transformations in recent years, influenced by technological advancements, shifting audience behaviours, and evolving socio-political landscapes. The theoretical frameworks that have traditionally guided scholarly discourse on media practices are now facing scrutiny as to their adequacy in explaining and predicting the complexities inherent in the present-day Nigerian media environment. The study adopts a comprehensive analysis of current media trends, the research aims to elucidate the extent to which Theories X, Y, and Z align with, or require modification to reflect, the intricacies of the contemporary Nigerian media landscape. Key focal points include the impact of digitalization on media consumption patterns, the role of social media in shaping public discourse, and the media's response to socio-political changes. Ultimately, this research strives to provide a nuanced understanding of the applicability of existing theoretical frameworks in the context of the rapidly evolving media industry in Nigeria, offering a foundation for future theoretical developments and empirical investigations in the field. The study recommended a collaborative approach to provide diverse insights and ensure that the re-examination process is inclusive and reflective of real-world experiences.